HUBUNGAN KREDIBILITAS BEAUTY INFLUENCER TASYA FARASYA TERHADAP SIKAP FOLLOWERS INSTAGRAM @SKINTIFICID - Higa Askamal (2023)
The credibility of an influencer cannot be judged only by the large number of followers, but by their qualified credibility. It is important for influencers to have credibility so that followers are persuaded by what is being informed so that attitudes change. Many influencers are considered not to have this capacity. It is not uncommon for audiences to question the veracity of reviews of endorsed products submitted by influencers who are considered to be not neutral. This study has a goal, namely, to find out whether there is a relationship between the credibility of beauty influencer Tasya Farasya and the attitude of Instagram followers @skintificid. This study uses the Source Credibility Theory put forward by Hovland, Janis, Kelley with three components, namely trustworthiness, expertise, and attractiveness. The sample technique used is the Proportional Random Sampling method. The results of this study indicate that Tasya Farasya's credibility fulfills three dimensions of changes in followers' attitudes, namely, cognitive, affective, conative. The dimension that has a significant relationship to the attitude variable of followers is the cognitive dimension. This research also shows that Tasya Farasya's credibility fulfills the three dimensions of credibility, namely, trustworthiness, expertise, and attractiveness. The most significant dimension is the attractiveness dimension. The conclusion of the study is that the credibility of beauty influencers has a relationship with the attitude of @skintificid Instagram followers.